Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.2 - Addition and Subtraction of Rational Numbers - Problem Set 2.2 - Page 58: 89



Work Step by Step

We first apply the distributive property. Then, we simplify the resultant expression: $n+\frac{4}{3}n-\frac{1}{9}n$ =$n(1+\frac{4}{3}-\frac{1}{9})$ =$n(\frac{1(9)+4(3)-1(1)}{9})$ =$n(\frac{9+12-1}{9})$ =$n(\frac{21-1}{9})$ =$n(\frac{20}{9})$ =$\frac{20}{9}n$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.